1999
DOI: 10.1172/jci5150
|View full text |Cite
|
Sign up to set email alerts
|

Expression of specific chemokines and chemokine receptors in the central nervous system of multiple sclerosis patients

Abstract: Chemokines direct tissue invasion by specific leukocyte populations. Thus, chemokines may play a role in multiple sclerosis (MS), an idiopathic disorder in which the central nervous system (CNS) inflammatory reaction is largely restricted to mononuclear phagocytes and T cells. We asked whether specific chemokines were expressed in the CNS during acute demyelinating events by analyzing cerebrospinal fluid (CSF), whose composition reflects the CNS extracellular space. During MS attacks, we found elevated CSF lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
753
5
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 943 publications
(806 citation statements)
references
References 71 publications
39
753
5
9
Order By: Relevance
“…Therefore, increased production of RANTES would be predicted to result in enhanced recruitment of proinflammatory cells to the target site, precipitating an amplified local inflammatory reaction. This is consistent with data showing that its expression is upregulated in several inflammatory conditions, such as rheumatoid arthritis 17 and multiple sclerosis, 18 as well as asthma. [8][9][10][11] Our data indicated that −403 A is more common in asthmatics, both atopic and non-atopic.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, increased production of RANTES would be predicted to result in enhanced recruitment of proinflammatory cells to the target site, precipitating an amplified local inflammatory reaction. This is consistent with data showing that its expression is upregulated in several inflammatory conditions, such as rheumatoid arthritis 17 and multiple sclerosis, 18 as well as asthma. [8][9][10][11] Our data indicated that −403 A is more common in asthmatics, both atopic and non-atopic.…”
Section: Discussionsupporting
confidence: 93%
“…As shown in Figure 1A (dark bars), all patients with PND had elevated levels of CXCL10 (average = 2,054 pg/ml, range = 347–6,846 pg/ml). The CSF CXCL10 levels in our patients were similar to or in some cases higher than those reported previously in the literature for MS patients and were also higher than values seen in normal CSF 15. Although CSF CXCL10 elevation has been reported in other disease states,16, 17, 18 this is the first report to our knowledge that PND patients have elevated CSF CXCL10.…”
Section: Resultssupporting
confidence: 83%
“…In addition, a correlation between CSF CXCL10 levels and CSF leukocyte count has previously been observed in MS 15. Here, we hypothesized that a key source of CXCL10 in PND patient CSF might be T cells, given that both T cells and CXCL10 were elevated in CSF from PND patients (see Table 1 and Fig 1), and that we have previously seen CSF PND antigen‐specific T cell responses in these patients 5, 6, 23.…”
Section: Discussionmentioning
confidence: 67%
“…13 However, its intense expression was shown in T cells isolated from synovial fluid from patients with RA, from tissues of chronically inflamed vaginal and colonic mucosa, or from cerebrospinal fluid from patients with multiple sclerosis. 14,15 Activated Th1/Tc1 subsets have been shown to express CXCR3 and CCR5. 14,16,17 Genetic contribution of chemokine receptor polymorphisms to several human disorders has been reported, such as CCR5-⌬32 allele associated with protective effect from human immunodeficiency virus (HIV)-1 infection.…”
Section: Introductionmentioning
confidence: 99%